Керамические клейма из Надлиманского городища (дополнение) - Матеевич, Н.; Редина, Е.Ф. (Материалы по археологии Северного Причерноморья, 2015)
This article treats epigraphic material that is supplementary to the finds published in the our monograph on Nadlymanske fortified settlement (IV-III century BC), situated in the Lower Dniester region (Dzys-Raiko, Okhotnikov, Redina 2012). There are 48 amphorae stamps included in this catalogue. A total number of amphorae sherds with stamps equals 221 items. Shares of different production centres remained the same, when compared with previously published collection.